Graphene Quantum Dot‐Protected Cadmium Selenide Quantum Dot‐Sensitized Photoanode for Efficient Photoelectrochemical Cells with Enhanced Stability and Performance. Issue 7 (2nd April 2015) - Yoon, Ki‐Yong; Ahn, Hyo‐Jin; Kwak, Myung‐Jun; Thiyagarajan, Pradheep; Jang, Ji‐Hyun
<x xml:space="preserve">Abstract</x> Graphene quantum dots (GQDs) are applied as an inexpensive and efficient hole transporter/extractor to improve the stability in cadmium selenide (CdSe) quantum dot‐based photoelectrochemical systems. By depositing GQDs on CdSe QD‐based electrodes, photochemical stability and photocurrent density are greatly enhanced, showing the visible working capability.